Impact Assessment of Pandemic Covid-19 on Four Typologies of Tourism Villages in The Special Region of Yogyakarta - Putri, Shinta Permana (E-Journal of Tourism; Volume 10 Number 2 (September 2023), 2023)
The pandemic has caused dramatic changes in the tourism sector globally including tourist villages. This study aims to identify the impact of the Covid-19 pandemic on four typologies of tourist villages in DIY, both positively and negatively. This research is qualitative research. Data was collected through interviews with the head of the tourist village. Content analysis is an analytical technique used in this study. The results of the study show that the COVID-19 pandemic does not always have a detrimental impact but also creates opportunities for tourism village communities to make sustainable progress. The positive impact of Covid-19 on tourist villages can be seen in terms of finance, environment, social cohesion, youth participation, product innovation, management/regulation changes, facilities, networking, and increasing technology use. Even so, Covid-19 still leaves new challenges for tourist villages to face a new era of post-pandemic tourism. These results certainly have implications for the practice of developing tourist villages in DIY in the future.